Sports photography : from snapshots to great shots - Frakes, Bill (Peachpit Press, 2013)
In Sports Photography: From Snapshots to Great Shots , author and sports photographer Bill Frakes shows you how to capture the key elements of sports photographs–motion and emotion, style and scene, place and purpose–whether you're at a baseball tournament, a track meet, or a professional football game. Starting with the basics of equipment, camera settings, and exposure, Bill covers the fundamental techniques of sports photography–understanding lighting, handling composition and focus, and timing peak action. He explains how to choose a shooting position on the field of play, identify the defining moments away from the action, and learn the etiquette of covering live sporting events. He then breaks down the shooting processes of specific sports, outlining the challenges and demands of each and showing how to isolate individual athletes in action. Beautifully illustrated with large, vibrant photos, this book teaches you how to take control of your photography to get the sports photo you want every time you pick up the camera. Master the photographic basics of composition, focus, depth of field, and much more Get tips on shooting with long and short lenses, learning when to use them and why Learn key techniques for photographing various sports, including football, baseball, basketball, soccer, and more Fully grasp all the concepts and techniques as you go, with assignments at the end of every chapter And once you've got the shot, show it off! Join the book's Flickr group to share your photos and ideas for great sports shots at flickr.com/groups/sportsphotographyfromsnapshotstogreatshots.